Perbedaan Harga Saham Sebelum dan Sesudah Pembagian Dividen pada Perusahaan Sektor Properti dan Real Estate yang Terdaftar di Bursa Efek Indonesia Periode Tahun 2014-2019 - Alfu Laila; Zarah Puspitaningtyas; Didik Eko J (Program Pasca Sarjana Unej, 2020)
Abstract The economic progress of a country is reflected in the capital market activities in that country. Economic progress as described on the basis of the market function as a capital transaction infrastructure that can affect a country's economic development. This study aims to see and analyze stock prices before and after dividend distribution listed on the Indonesia Stock Exchange (IDX). This study uses a comparative analysis with a quantitative approach. The data source used is secondary data. This data is obtained from the official website of the Indonesia Stock Exchange (Internet Data Exchange / BEI). The results of this study indicate that there are significant differences in stock prices before and after dividend distribution. This is based on the test results on the paired sample t-test which shows the significance value is smaller than the alpha value a (0.000 <0.05) so that Ho is rejected and Ha is accepted. Keywords: Stocks, Dividends, BEI.